Mini Research on Earthquake Alert at Jumbara PMI - Usiono, Usiono; Putri, Devita Aulia; Hasanah, Nurul; Purba, Tiara Paramita BR. (Universitas Ibn Khaldun, 2024)
Earthquakes are a natural phenomenon that often occurs in Indonesia due to the interaction of tectonic plates. Indonesia's geography, which meets four of the world's tectonic plates, makes it prone to earthquakes. Preparedness in dealing with disasters is important, especially in schools as education and awareness centers. Children, as rapid learners, can be agents of change in shaping hazard awareness and disaster preparedness. This study aims to understand the opinions of the PMI Jumbara committee about disaster preparedness, describe the definition of disaster preparedness, and analyze factors related to earthquakes. Through a qualitative approach and interviews with five members of PMI's Jumbara committee, the results highlight actions to be taken during and after the earthquake, explain the factors that cause earthquakes, and strengthen the urgency of preparedness in facing disasters in Indonesia. In conclusion, preparedness and understanding of the right action during an earthquake are important in reducing the adverse effects of natural disasters.